Normalized power correlation for a vertical axis wind turbine with varying geometries - Tsang, E. (CRC Press, 2009)
This article uses dimensional analysis and numerical predictions to obtain a turbine-specific correlation for the ZVAWT. The correlation will predict turbine's power coefficient after changes to critical features, proving to be a valuable design tool that can be extended to other types of turbines for the purpose of predicting performance over a range of operating conditions.